Epidemiology of Invasive Fungal Disease by Aspergillus in a University Hospital in Santiago – Chile, During the Period 2005–2015. (4th October 2017) - Valenzuela, Pablo; Rabagliati, Ricardo; Legarraga, Paulette
Abstract: Background: In Chile, there is little information on invasive fungal disease (IFD) due to filamentous fungi. A study of our institution showed 41 episodes in hemato oncological patients between the years 2004 and 2008, being the main cause Aspergillus, but the epidemiological characteristics of this infection in Chilean patients are not currently known. The objective describes the epidemiology of IFD by Aspergillus in our center. Methods: Retrospective study in adults patients hospitalized in our center, diagnosed with IFD by Aspergillus between 2005 and 2015. Medical records of identified cases were review, incidence were calculated with the discharges numbers and total numbers of IFD. The study was approved by the Institutional Ethics Committee. Results: Sixty-seven cases were identified, with an incidence of 2.53 per 10, 000 discharges between 2005 and 2015, with 35 cases of IFD in the period 2005–2010 and 32 cases in the period 2011–2015. The etiologies were A. fumigatus 42%, A. flavus 7%, A. terreus 7%, A. niger 3%, and Aspergillus spp. 40%. According EORTC/MSG criteria, 39% were proven, 52% probable, and 9% possible. The 55% of patients were male, the mean ± SD age was 51 ± 18 years, 57% had hematological conditions, mainly acute leukemias, rheumatological conditions in 15% and solid organ transplant in 13%, neutropenia under 500/mm 3 in 37% and serum galactomannan test >0.5 in 67%. The clinical focus was 73% pulmonary and 17% rhinosinusal. The treatment was 81% monotherapy, 73% with voriconazole, 15% with liposomal amphotericin B and 6% with caspofungin. The 30 days mortality was 39%. Conclusion: The epidemiology of IFD by Aspergillus is similar to that described in developed countries, in highly vulnerable patients with a mortality close to 40%. More epidemiological information from other hospitals is necessary to complete the epidemiology of Aspergillus infections in our country. Disclosures: All authors: No reported disclosures.